Les classes moyennes tunisiennes entre mythe et réalité.Éléments pour une mise en perspective historique - Baccar Gherib (L’Année du Maghreb)
In Tunisia, middle classes were ever-present in the political discourse. The regime justified their economic and social policies with the continued expansion of the middle class that included, according to them, 80% of Tunisians. We believe, however, that this rate must be questioned. We observed, at first, that the theme of social class is absent from the academic field. This we explained by the repression of the approach in terms of social classes with roots in the political and social history of modern Tunisia. We then discussed different definitions of the middle class and showed that they prove difficult to match the declared rate. We also offered a historical perspective of the theme that ties the expansion and prosperity of the middle classes to the different mutations of Tunisian capitalism. Finally, we described the main changes that contribute today to the weakening and destabilization of the middle class in Tunisia.